Living Hadis Study on the Tulak Breuh Tradition in the Dead Management Procession in Manyak Payed Aceh Tamiang - Ataillah Ataillah; Muhammad Reza Fadil; Nawawi Marhaban (Al-Bukhari : Jurnal Ilmu Hadis, 2021)
This study describes the phenomenon of the tulak breuh tradition in the procession of taking care of the dead in Manyak Payed District, Aceh Tamiang Regency as a living hadith phenomenon. This tradition still raise questions in the aspect of dalil that forms the basis for the practice. However, people still practice this tradition because in their opinion it is in accordance with the hadith and the understanding of the fiqh scholars in kitab kuning. This study aims to find out the argument for the implementation of the tradition and how it is practiced in the society. Qualitative research with a living hadith approach is used to reveal the practice of this tradition. In addition to conducting a literature review, the interview method was also used to collect data. The results showed that the practice of tulak breuh in Manyak Payed district, Aceh Tamiang regency was assumed to be a way to accommodate the fidyah shalat for people who died. The procedure is to refuse rice (tulak breuh) which is placed on a wheeled place that allows it to be shifted from one person to another until it reaches the number of fidyah shalat left behind. This tradition has been practiced for generations and run consistently. From the side of the argument, the hadith mauqūf from Ibn 'Abbas ra. used as the basis for implementation. From a living hadith perspective, understanding this hadith forms a tradition in the procession of taking care of the dead in Manyak Payed District, Aceh Tamiang Regency.